DESAIN DAN PENGEMBANGAN MEDIA EDUKATIF TEMATIK BERBENTUK “PHYGITAL” UNTUK MENINGKATKAN PEMBELAJARAN ANAK USIA DINI TENTANG PROFESI PILOT (LPPM Institut Desain dan Bisnis Bali, 2024)
This study aims to design a thematic phygital educational media with a pilot theme that includes content in English, mathematics, and basic science for early childhood education. The pretend play method approach is used in the development of this educational media, with a focus on applying the symbolic play approach in various forms of physical and digital educational media. The research method used is research through design. The study involves the stages of designing educational media, testing, and evaluation through user testing. Through the process of developing educational media, interesting findings were obtained, indicating that phygital educational media with a pretend play approach provides an interactive and enjoyable learning experience for children. The study identifies four important components in building effective symbolic play: story, props, dolls, and sufficient time. The results of this study contribute to the development of effective and engaging teaching methods for early childhood education. The study also provides an understanding of the application of symbolic play approach in physical and digital educational media, providing a foundation for the development of more innovative educational media in the future.